Intra- and Extra-Hospital Dissemination of IMP-22-Producing Klebsiella pneumoniae in Northern Portugal: The Breach of the Hospital Frontier Toward the Community - Gonçalves, Daniela; Cecílio, Pedro; Faustino, Alberta; Iglesias, Carmen; Branca, Fernando; Estrada, Alexandra; Ferreira, Helena (Frontiers in Microbiology, 2021)
The emergence of infections (and colonization) with Enterobacteriaceae-producing carbapenemases is a threatening public health problem. In the last decades, we watched an isolated case becoming a brutal outbreak, a sporadic description becoming an endemic problem. The present study aims to highlight the dissemination of IMP-22-producing Klebsiella pneumoniae in the North of Portugal, through the phenotypic and genotypic characterization of isolates collected from hospitalized patients (n=5) and out-patients of the emergency ward of the same acute care hospital (n=2), and isolates responsible for the intestinal colonization of residents in a Long-Term Care Facility (n=4). Pulsed-field gel electrophoresis (PFGE) results, associated with conjugation experiments pointed to a pattern of both vertical and horizontal dissemination. Overall, and complementing other studies that give relevance to IMP-22-producing K. pneumoniae in the clinical settings, here we show for the first time the public health threatening breach of the hospital frontier of this resistance threat, toward the community.